Polyaniline-based flexible implantable electrodes for neural sensing/stimulation applications - Almufleh, Nader Lutfi (2021)
A Master of Science thesis in Biomedical Engineering by Nader Lutfi Almufleh entitled, “Polyaniline-based flexible implantable electrodes for neural sensing/stimulation applications”, submitted in March 2021. Thesis advisor is Dr. Amani Al-Othman and thesis co-advisors are Dr. Hasan Awad Moh’d Al Nashash and Dr. Mohammed Hussein Al-Sayah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).